What is effective in promoting a healthy lifestyle in secure psychiatric settings? A review of the evidence for an integrated programme that targets modifiable health risk behaviours. Issue 3 (8th August 2016) - Long, Clive; Rowell, Arleen; Rigg, Samantha; Livesey, Frank; McAllister, Peter
Abstract : Purpose: – The purpose of this paper is to describe healthy lifestyle initiatives in a secure psychiatric facility and the evidence base for these interventions. Design/methodology/approach: – Following a detailed review of the literature on the physical health of psychiatric inpatients, a trans-diagnostic approach to behaviour change is advocated in selected areas. Findings: – Lifestyle strategy proposals were produced that incorporate the principle of "libertarian paternalism" in making changes to eating and exercise behaviour; a programme of motivational and reinforcement strategies; and facility-specific environmental restructuring to include maximising the therapeutic use of green space. Practical implications: – Instituting described changes needs to be accompanied by a programme of evaluation to assess intervention-specific physical health changes. Originality/value: – This paper provides a synthesis of findings in key areas of behaviour change relevant to improving the physical health of psychiatric patients in secure settings. It is a co-ordinated and interlinked lifestyle strategy that has applicability to similar services.